Stress assessment in Latin American fish through cortisol response levels (Revista Científica Ciencias Naturales y Ambientales, 2024)
Fish, both wild and farmed, face stress factors that alter their homeostasis and ability to adaptin natural and captive environments, putting their survival at risk. Pollution and changes in waterquality affect their health and response to stress. In this area, cortisol is a glucocorticoid releasedby the hypothalamic-pituitary-interrenal axis, which is key in the response to stress and everythingrelated to its survival. The objective of this review was to analyze stress in fish from Latin Americaand the cortisol response. The analysis showed that the studies have been carried out in Brazil 77%,Colombia 10%, and Ecuador, Mexico, Uruguay and Chile, with 3% respectively. 13 studied speciesare reported, corresponding to: Brycon amazonicus, B. cephalus, Piaractus mesopotamicus, P.brachypomus, Colossoma macropomum, Rhamdia quelen, Pimelodus maculatus, Oreochromisniloticus, O. mossambicus, Morone saxatilis, Arapaima gigas, Austrolebias reicherti and Salmo salar. The fish species analyzed in Latin America are mostly native, with the main stressors identifiedbeing hypoxia, persecution, transportation and handling, which increase cortisol levels. However,the use of additives such as clove oil, β-glucans and ascorbic acid helps reduce this elevation. Itis important to note that although chemical anesthetics such as MS-222, although they reducestress, affect processes such as reproduction. However, the use of essential oils such as clove oilor β-glucans help reduce stress indices, so essential oils could be an alternative without negativeeffects on some other physiological functions.
Keywords: fish, Latin America, cortisol, stress.; fish; Latin America; cortisol; stress